2019
DOI: 10.1016/j.mex.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro method to evaluate hemolysis of human red blood cells (RBCs) treated by airborne particulate matter (PM10)

Abstract: Air pollutants are capable to enter bloodstream through the nose, mouth, skin and the digestive tract. Hemolysis is the premature destruction of red blood cells (RBCs) membranes. This can affect metabolism of RBCs and reduce cell life. Each of these adverse effects could lead to anemia, jaundice and other pathological conditions. Hemolysis can induce by the mineral components adsorbed on the particles. The aim of this study was to evaluate hemolysis of RBCs treated by airborne PM 10 (PM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 4 publications
1
29
0
Order By: Relevance
“…After centrifugation, the supernatant incubated with hybrid hydrogels or fibrin gels after 24 h showed a light red color similar to that of the saline treatment (control), indicating the good hemocompatibility of the hybrid hydrogels (Figure 4D). Furthermore, the percentage hemolysis of the hybrid hydrogels was within the safe limit for hemostatic biomaterials reported in the literature [24] (Figure 4E).…”
Section: Excellent In Vitro Blood Clotting and Biocompatibility Of Th...supporting
confidence: 72%
“…After centrifugation, the supernatant incubated with hybrid hydrogels or fibrin gels after 24 h showed a light red color similar to that of the saline treatment (control), indicating the good hemocompatibility of the hybrid hydrogels (Figure 4D). Furthermore, the percentage hemolysis of the hybrid hydrogels was within the safe limit for hemostatic biomaterials reported in the literature [24] (Figure 4E).…”
Section: Excellent In Vitro Blood Clotting and Biocompatibility Of Th...supporting
confidence: 72%
“…As shown in Figure , in the 4‐hour exposure system, the experimental results showed that when the UFCB concentration was lower than 40 mg/L, the hemolysis ratio of hRBCs would not be induced. UFCB could not significantly change the permeability of hRBCs membrane, which means that the membrane was not completely destroyed . The damage to hRBCs was relatively low, providing a guarantee for the following experimental determination.…”
Section: Resultsmentioning
confidence: 91%
“…Similarly, in our previous study, elevated neutrophils counting indicated that PM served as an external stimulant to the body, inducing inflammatory responses (Jiang et al, 2020). Hemolysis is the premature destruction of red blood cells (RBCs) membranes and it can be induced by the mineral components adsorbed on the particles (Mesdaghinia et al, 2019). In the current study, no significant changes were observed in the relevant red blood cell index, which indicates that PM did not cause the destruction of RBCs.…”
Section: Discussionmentioning
confidence: 73%